The history of Africa the quest for eternal harmony - Asante, Molefi Kete. (New York Routledge, 2014)
There is a paradox about Africa: it remains a subject that attracts considerable attention yet rarely is there a full appreciation of its complexity. African historiography has typically consisted of writing Africa for Europe―instead of writing Africa for itself, as itself, from its own perspectives. The History of Africa redresses this by letting the perspectives of Africans themselves take center stage. Authoritative and comprehensive, this book provides a wide-ranging history of Africa from earliest prehistory to the present day―using the cultural, social, political, and economic lenses of Africa as instruments to illuminate the ordinary lives of Africans. The result is a fresh survey that includes a wealth of indigenous ideas, African concepts, and traditional outlooks that have escaped the writing of African history in the West. The new edition includes information on the Arab Spring, the rise of FrancAfrica, the presence of the Chinese in Africa, and the birth of South Sudan. The chapters go up to the present day, addressing US President Barack Obama's policies toward Africa. A new companion website provides students and scholars of Africa with access to a wealth of supporting resources for each chapter, including images, video and audio clips, and links to sites for further research. This straightforward, illustrated, and factual text allows the reader to access the major developments, personalities, and events on the African continent. This groundbreaking survey is an indispensable guide to African history.
Includes bibliographical references (pages 382-386) and index.
Keywords: Africa--History.